Cohort of estrogen-induced microRNAs regulate adrenomedullin expression - Wetzel-Strong, Sarah E. (Am J Physiol Regul Integr Comp Physiol, 2015)
Estrogen regulates the expression of many genes and has been correlated with differences in cardiac contraction; however, the underlying mechanisms remain poorly defined. Adrenomedullin (Adm = gene; AM = protein) is a multifunctional peptide with inotropic actions. Previous studies have demonstrated that estrogen enhances the expression of Adm, suggesting a relationship between AM and estrogen in cardiac contraction during physiological and pathological states. In this study, female mice in a mouse model of genetic Adm overexpression, abbreviated as Adm(hi/hi), were found to express 60 times more Adm in the heart than wild-type littermates, compared with the three-fold elevation of Adm previously reported in Adm(hi/hi) male hearts. Thus, this study sought to further investigate any functional consequences of increased cardiac Adm expression and begin exploring the mechanisms that regulate Adm expression in an estrogen-dependent fashion. This study revealed that heart function is enhanced in Adm(hi/hi) females, which along with Adm expression levels, was reversed following ovariectomization. Since the Adm(hi/hi) line was generated by the displacement of the 3′ untranslated region (UTR), the native 3′UTR was examined for estrogen-induced microRNAs target sites to potentially explain the aberrant overexpression observed in Adm(hi/hi) female hearts. Using a bioinformatic approach, it was determined that the mouse Adm 3′UTR contains many target sites for previously characterized estrogen-induced microRNAs. This study also determined that the novel microRNA, miR-879, is another estrogen-induced microRNA that interacts with the 3′UTR of Adm to destabilize the mRNA. Together, these studies revealed that estrogen-induced microRNAs are important for balancing cardiac Adm expression in females.